Otoritas Karismatik Dalam Pembentukan Ruang Sakral: Studi Kasus Abah Guru Sekumpul Di Martapura - A Gaus Rafsanjani -; Akhmad Siddiq (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2026)
Martapura is renowned as a religious city imbued with sacred values. The collective awareness of the community regarding the figure of Abah Guru Sekumpul has led the entire urban space to be regarded as sacred, not merely the area surrounding his tomb. illustrates how religion functions to create social order through symbols, rituals, and solidarity. This research applies a qualitative approach through literature review, field observation, and interviews with communities in South Kalimantan. Previous studies mostly examine rituals or religious figures in isolation and rarely explore how sacredness expands into a city-wide collective identity. Research that connects the sacred–profane concept with urban spatial dynamics in Martapura also remains limited. Within the framework of Émile Durkheim's sacred–profane theory, this phenomenon The study reveals that the sacredness of Martapura is shaped by social interactions, Islamic boarding school (pesantren) education, and local government policies that instill religious values in daily life. This sacralization process occurs through the internalization of religious values in social interactions across both younger and older generations, thereby transcending the physical boundaries of the tomb and evolving into a collective identity of the local community. The tomb of Abah Guru Sekumpul serves as a spiritual center that binds the community together through mechanical solidarity grounded in morality and spirituality. This sacredness renders Martapura not only a religious city but also a living social space sustained by its residents' shared consciousness of divine values and Islamic tradition.